'You see the empty bed which means it's either a transplant or a death': a qualitative study exploring the impact of death in the haemodialysis community. Issue 6 (22nd June 2021) - Sutherland, Sheera; Durley, Kirsty E; Gillies, Kirsty; Glogowska, Margaret; Lasserson, Daniel S; Pugh, Christopher; Lowney, Aoife C
Abstract : Objective: To explore the impact of the death of a patient in the haemodialysis unit on fellow patients. Methods: We interviewed patients on dialysis in a tertiary dialysis centre using semistructured interviews. We purposively sampled patients who had experienced the death of a fellow patient. After interviews were transcribed, they were thematically analysed by independent members of the research team using inductive analysis. Input from the team during analysis ensured the rigour and quality of the findings. Results: 10 participants completed the interviews (6 females and 4 males with an age range of 42–88 years). The four core themes that emerged from the interviews included: (1) patients' relationship to haemodialysis, (2) how patients define the haemodialysis community, (3) patients' views on death and bereavement and (4) patients' expectations around death in the dialysis community. Patients noticed avoidance behaviour by staff in relation to discussing death in the unit and would prefer a culture of open acknowledgement. Conclusion: Staff acknowledgement of death is of central importance to patients on haemodialysis who feel that the staff are part of their community. This should guide the development of appropriate bereavement support services and a framework that promotes the provision of guidance for staff and patients in this unique clinical setting. However, the authors acknowledge the homogenous sample recruited in a single setting may limit the transferability of the study. Further work is needed to understand diverse patient and nurse experiences and perceptions when sharing the knowledge of a patient's death and how they react to loss.